Comparative Supreme Justice - Tamm, Ditlev (Oñati Socio-Legal Series, 2011)
This article deals with the great variety of Supreme Courts in the world today and presents some selected courts. Supreme Courts are found in most countries both as only apex courts or in a courts’ system where also supreme administrative courts or constitutional courts are found. The starting point is the variation of supreme justice in the Nordic countries where one apex court is the system of Denmark and Norway whereas administrative courts are found in Sweden and Finland. Constitutional courts stem from the European tradition and are most abundant in Europe and in countries with a civil law system but especially in Africa they are also found in common law countries. Mexico is mentioned as a specific example of a Supreme Court that has taken upon itself to be a main player in the endeavour to communicate the law to a general audience. The article is a presentation with samples of what is going to be a project on comparative supreme justice in which the position of supreme courts in the various states, the recruitment scheme and competence of the courts and other such factors will be analyzed on a global basis.